Kajian Rasio EPC dan Ce c Sebagai Prediktor Disfungsi Endotel pada Pasien dengan Kelompok Risiko Tinggi Berdasarkan Framingham Risk Score 10 Years - Wiwit Nurwidyaningtyas; Djanggan Sargowo; Achdiat Agoes; Titin Andri W; S Satuman (The Indonesian Heart Association, 2013)
Research background. Circulating Endothelial Cells (CEC) is a reflection of endothelial damage or endothelial stress, increasing of CEC amount depend on endothelial mechanism, edothelial adhesivity damage and cellular apoptosis as a result of decreasing sitoskleleton function. If higher exposure affects the increasing of CEC amount,VEGF other growth factor mediators will be reflected as endothelial stress manifestation which roles in the increasing of re-population and Endothelial Progenitor Cells (EPC) differentiation. Endothelial Progenitor Cells is a mononuclear cell (a part of stem cell) that could change to be mature endothel and roles in re-edothelialisation and neovascularisation. This research aimed to investigate the ratio of EPC : CEC in risk group through Framingham Risk Score (FRS) 10 years approach as endothelial dysfunction predictor.Research method and result. There were 55 research subjects whom taken by FRS scoring and devided into some risk groups and two control groups. They were control group I (health) and control group II (sick). Base blood was taken to every each of them to analyze their EPC and CEC with Flowcytometry. EPC was analyzed by CD34 Per CP Santa Cruz SC-19621 and CD 133 FITC (fluorescein isothiocyanate) Bioss bs-0395R-FITCmarker.WhileCEC was analyzed CD45 FITC Biolegend 202205 dan CD 146 PE Biolegend 134704 marker. Result showed, there was significant ratio differences of EPC : CEC in those six groups which was proven by p-value 0.032< ? (0.05). The higher ratio was in high risk group (139.06).Conclusion. Research showed that EPC amount was increase related to the increasing of high risk level according to FRS 10 years, but its increasing did not followed by its ability to homing in injury area as role part in re-endothelialisation process. It found that EPC amount was higher in high risk group than in low risk group.